PENGARUH IMPLEMENTASI APLIKASI SISTEM INFORMASI KINERJA APARATUR (SIKAP) TERHADAP DISIPLIN KERJA GURU PADA SEKOLAH DASAR NEGERI KECAMATAN BATANG ANAI - Dea Ananta; Tia Ayu Ningrum; Syahril Syahril; Novriyanti Achyar (STKIP Pesisir Selatan, 2026)
Objective: One problem of teachers’ work discipline is tardiness and irregular performance reporting, indicating the need for a technology-based monitoring system. This study aims to analyze teachers’ discipline, examine the implementation of SIKAP, and its effect. A quantitative survey method was used. The results show that SIKAP implementation significantly affects teachers’ work discipline. The novelty lies in using SIKAP as a technology-based monitoring system in elementary schools. Methods: This research used a quantitative approach with a positivist paradigm. The population was 288 civil servant teachers, with 174 respondents selected through cluster random sampling. Data were collected using Likert-scale questionnaires and analyzed with descriptive and inferential statistics, including validity, reliability, normality, t-test, F-test, and coefficient of determination (R²). Results: The results show that teacher work discipline is in the good category, while SIKAP implementation is fairly good to good. Hypothesis testing indicates that SIKAP has a significant effect on teacher discipline (sig. 0.000 < 0.05), with an R² value of 0.718, meaning 71.8% of discipline is influenced by SIKAP implementation. Novelty: This study emphasizes the importance of digital performance management systems in improving teacher discipline by linking technology implementation with behavioral outcomes in education.